Recycling Engineering of PCBs for Copper Recovery - Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr.; Mohamed Zulkali, Mohamed Daud, Assoc. Prof. Dr.; Alina Rahayu, Mohamed; Zarina, Zakaria, Dr.; Khairul Farihan, Kasim; Ku Syahidah, Ku Ismail; Farizul Hafiz, Kasim (Malaysian Invention and Design Society (MINDS), 2010)
Brig. Jen. Dato' Prof. Dr. Kamarudin Hussin and his team from School of Bioproses Engineering won silver for Recycling Engineering of PCBs for Copper Recovery. ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.